2015
DOI: 10.1038/srep13120
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the Regulatory Region of WNT5A Reduced Risk of Cardiac Conotruncal Malformations in the Chinese Population

Abstract: WNT5A is one of the most highly investigated non-canonical Wnt ligands and is involved in the embryonic heart development, especially in formation of the cardiac conotruncal region by regulating the migration and differentiation of cardiac neural crest (CNC) and second heart field (SHF) cells. No study to date has comprehensively characterized the WNT5A regulatory variants in patients with congenital heart malformations (CHMs). The association between regulatory variants of the WNT5A gene and CHMs was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…et al . observed that rs371954924 in WNT5A reduced gene expression by attenuating the binding affinity of the transcription factor SOX9 43 . In our previous study, we identified a functional RARE in the Cx43 promoter 23 .…”
Section: Discussionmentioning
confidence: 96%
“…et al . observed that rs371954924 in WNT5A reduced gene expression by attenuating the binding affinity of the transcription factor SOX9 43 . In our previous study, we identified a functional RARE in the Cx43 promoter 23 .…”
Section: Discussionmentioning
confidence: 96%
“…There are also reports of TBX1 cis -regulatory elements being involved in cardiac development [ 32 , 33 , 51 , 62 ], such as a mutation of the Fox-binding site upstream of Tbx1 abolishing Tbx1 expression in the pharyngeal endoderm [ 32 , 33 ] and heterozygous variants NC_000022.11:g.19756055C > T and NC_000022.11: g.19756212A > C upstream of the TBX1 TSS in VSD patients significantly decreasing the activity of the TBX1 gene promoter [ 51 ]. In addition, studies have reported that variants in the regulatory region of other OFT development-related genes are also associated with CTD, such as WNT5A [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would further support the finding that Wnt5a misexpression is a key contributor to D-TGA. In a previous study of 1210 patients with congenital heart malformations, Li et al 12 also found that reduced levels of Wnt5a lead to lower rates of conotruncal malformation. While this study did not specifically examine patients with D-TGA, the results support the work described by Škorić-Milosavljević et al Interestingly, the authors did not find evidence of any affected ciliary genes at their pathogenic locus, despite prior studies finding several ciliary genes as a key component of TGA.…”
mentioning
confidence: 94%